Plasmonic/Magnetic Multifunctional nanoplatform for Cancer Theranostics - Ravichandran, M.; Oza, Goldie; Velumani, S.; Ramirez, Jose Tapia; García Sierra, Francisco; Andrade, Norma Barragan; Vera, A.; Leija, L.; Garza Navarro, Marco Antonio (2016)
Cancer is the second leading disease which causes major mortality and morbidity worldwide1 . In cancer therapy, it is crucial to increase the drug specificity and drug efficacy to minimise or completely eradicate significant side-effects on patients2 . Cancer nanotherapeutics overcome many serious drawbacks of chemotherapy such as non-specific targeting, lower efficacy, insolubility of drug moieties in water and oral bioavailability3 . Accordingly, Superparamagnetic Iron Oxide Nanoparticles (SPIONs) are exploited as an important nanomaterial for cancer detection as well as therapeutics4 . Such magnetic nanoparticles (NPs) gained its momentum because of their single-domain ordering along with their large surface to volume ratio (providing large surface area for attachment of biological entities). Hence, this property makes them a suitable candidate as a contrast agent, drug-carrying cargo and hyperthermal agent5 .